Rain models for the prediction of fade duration at millimeter wavelengths - Othman, Mohd. Afzan (2006)
The planning of radio communications system requires an estimate of the average annual outage due to fading, which at millimeter wavelengths, is generally dominated by the effects of rain attenuation. Current ITU-R recommendations provide algorithm for estimating the exceedance static of rain-induced attenuation on terrestrial links. Another factor of interest, not currently covered by ITU-R recommendations is the distribution of the durations of rain fades. Hence this project involved an extensive review on the available models describing annual rain fade distributions on line-of-sight links. Also, analysis on the rain attenuation data conducted on an experimental 350m, and 38GHz in frequency in UTM campus for 1 year will be used to obtain information on the rain fade statistic. Previous researches pointed out that the distribution of the durations of rain events at different intensities is more fundamental than distributions of link fades. Thus, this project aim is to establish an expression for the average number of events per year of rain intensity greater than a given threshold. This could be achieved from the detail analysis of the 38GHz link signal level profile database. Thus, the rain fade statistic describing annual rain fade distributions on line-of-sight could be developed. To predict rain attenuation on complex multi hop or route diverse links, it is necessary to have a statistical representative of rainfall in time and space, which is accurate over wide ranges of spatial and temporal scales. Various available statistical models will be used to demonstrate the influence of the developed rain fade statistic when applied for more complex microwave links